Equiaxed and Porous Thermal Barrier Coatings Deposited by Atmospheric Plasma Spray Using a Nanoparticles Powder1. Issue 4 (13th December 2013) - Gao, Yang; Gao, Jianyi; Yang, Deming
<x xml:space="preserve">Abstract</x> A novel coating with microstructure comprise equiaxed grains and multitudinous pores applied to thermal barrier coatings are developed by atmospheric plasma spray (APS) using spherical agglomerated and sintered powder made from nano‐particles of partially stabilized zirconia (YSZ). The coatings were then heated to 1100–1200 °C for thermal evaluation tests. Field emission scanning electron microscope and X‐ray diffraction were applied to analyze the nanostructured powder feedstocks and coatings. The results demonstrated that the coatings consisted of integrated fine equiaxed grains and multitudinous pores but not lamellar structure like conventional plasma sprayed ceramics. The size of equiaxed grain in the coatings varied in a large range and grain size slightly increased along with the rise of testing temperature and time. Moreover, the nanostructural equiaxed grains with the similar size of original nanoparticle, which surrounded the pores in the coatings undergoing solidification during plasma spraying were observed. The results of phase composition showed that the metastable tetragonal phase was the primary phase in nano YSZ coatings and does not change with the working environment. Furthermore, high temperature contributed to the increase of the microhardness of the coating.